Co-Cr-Mo-W powder obtained by mechanical alloying - Habibe,Alexandre Fernandes (2020)
ABSTRACT New techniques for manufacturing of biomaterials using additive/substrate manufacturing such as melting laser sintering (SLM) or CAD/CAM milling use micrometric metal powders to build custom parts. CoCrMo alloys are commonly used as biomaterials due to biocompatibility, high corrosion resistance and good mechanical properties. In this work, Cr-Co-based powder was obtained by mechanical alloying of Cr-Co-Mo-W alloy, using different Ball/Powder-Ratios (BPR) and thermal treatments. The powders were deagglomerated and characterized by X-ray diffraction (XRD) and Scanning electron microscopy (SEM). Based on SEM micrographs, the particle size analysis was used to compare the particles spheroidizing degree, using Feret’s diameter. The XRD patterns shown Co(solid-solution) as crystalline phase. The results of particles size indicates a decrease of Feret’s diameter in BPR (Ball/Powder-Ratio) from 4:1 to 6:1 understanding that from this ratio there is no significant decrease of this relation but there is an average size increase with losses in morphological aspect. The comparison between atomized powders and powder developed in this work indicates that atomized products present relation close to one which indicates there is uniformity in the particles spherical shape. Comparing ground powders from 6:1 ratio (before and after thermal treatment) there is a considerable decrease of Feret’s diameter being it decreased from 1.75 to 1.4, an increase of about 46% in particles spheroidizing.